Dual Ascent Algorithm-Based Improved Droop Control for Efficient Operation of AC Microgrid - Jiang, Yajie; Yang, Yun (Frontiers in Electronics, 2022)
In this work, the loss (including wire loss and converter loss) of island three-phase AC microgrid is modeled as a quadratic function of the current distribution coefficient, that is, a concave function with equality and inequality constraints. On the basis of the concave optimization principle, the optimal current distribution coefficient of the distributed energy unit (DEU) is calculated online by the double ascent optimization method (DAOM) to minimize the distribution loss. It is proven that the concave function with multi-variables can be optimized by the DAOM. Using the average reactive power distribution scheme, the optimal active power distribution coefficient with the minimum distribution loss of the AC microgrid can be obtained in real time. In addition, given the high R/X ratio in the short-distance AC microgrid, the active power–frequency (P-ω) droop control and reactive power–voltage amplitude (Q-E) droop control are not suitable for power distribution among DEUs. Thus, an advanced strategy comprising active power–voltage amplitude (P-E) droop control and reactive power-frequency (Q-ω) droop control is proposed to dispatch the output active powers and reactive powers of DEUs. Simulation examples are provided to verify the convexity of the proposed model and the effectiveness of the control strategy.